PERLINDUNGAN HUKUM BAGI PEMENANG LELANG OBJEK HAK TANGGUNGAN DALAM HAL EKSEKUSI TERHALANG OLEH GUGATAN DITINJAU DARI HUKUM jAMINAN - Mohammad Algifarri Sukmaya (Faculty of Law, Maranatha Christian University, 2020)
One way to settle bad debts is the execution mortgage rights through a public auction. However, in practice, the execution of mortgage security does not always provide legal protection to the auction buyers of mortgage rights, one of them is that the auction winner cannot enjoy his rights to the auction object because of the lawsuit over the execution of mortgage rights, so that the execution of the mortgage security cannot be carried out. The purpose of this research is to find out the position of the collateral right that has been auctioned in the event that there is a lawsuit from a third party and legal protection that can be given to the auction winner for the loss of not being able to enjoy the object of the mortgage rights auction due to a lawsuit from a third party. The research method used in this study is a normative juridical approach, which uses secondary data in the form of related legislation. Based on the research conducted, the results are: First, the position of the guaranteed mortgage rights object in the auction execution in the event that there is a lawsuit from a third party, legally still the right of auction winner that have a good faith. Second, legal protection for the winner of a bid in good faith over losses cannot enjoy the object of the mortgage right because the lawsuit can be carried out by litigation and non-litigation. Litigation lawsuits are based on unlawful acts against auction sellers.